Synthesis of Naltrexone and (R)-Methylnaltrexone from Oripavine via Direct Oxidation of Its Quaternary Salts - Machara, Ales; Werner, Lukas; Leisch, Hannes; Carroll, Robert J.; Adams, David R.; Haque, D. Mohammad; Cox, D. Phillip; Hudlicky, Tomas (Synlett, 2015)
(R)-Methylnaltrexone and naltrexone were each prepared in four steps from oripavine in practical yields. The procedure involved quaternization of oripavine with cyclopropylmethyl halides, singlet oxygen oxidation of the quaternary salts, and the reduction of endo peroxides to 14-hydroxyketone functionalities. (R)-Methylnaltrexone was prepared from the corresponding R-diastereomer of the oripavine salt. All diastereomeric mixtures of the quaternary salts were subjected to N-demethylation with sodium thiolate to yield cyclopropyl methylnororipavine, which was converted into naltrexone by peracid oxidation and hydrogenation according to established procedures.
Keywords: photochemical oxidation; singlet oxygen; naltrexone synthesis; (R)-methylnaltrexone synthesis; N-demethylation of oripavine quaternary salts